24. WOMEN’S KNOWLEDGE AND ATTITUDES REGARDING THE IMPLANON NXT® SUBDERMAL CONTRACEPTIVE IMPLANT (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess women’s knowledge and attitudes regarding the Implanon NXT® contraceptive implant at Transport Hospital (Vietnam) in 2024.Methods: A cross-sectional descriptive study was conducted among 200 women who sought counseling at the Department of Obstetrics and Neonatology in 2024. Knowledge and attitudes toward the implant were evaluated and categorized, and factors associated with better knowledge and favorable attitudes were examined (p < 0.05).Results: Overall, 58.5% of participants had poor knowledge, 34.0% had average knowledge, and 7.5% had good knowledge. Attitudes were unfavorable in 57.5% and favorable in 42.5% of respondents. Better knowledge and favorable attitudes were significantly associated with employment as officials/staff, university-level education, urban residence, and prior use of a contraceptive implant (p < 0.05).Conclusions: Women’s knowledge and attitudes toward the Implanon NXT® implant were generally limited. Strengthened counseling and targeted health communication are needed to improve awareness and effective uptake of this contraceptive method.